Two cases of systemic mantle cell lymphoma involving the skin - Viktoryia Kazlouskaya; Amy Spizuoco; Jacqueline M Junkins-Hopkins (Wolters Kluwer Medknow Publications, 2016)
Mantle cell lymphoma (MCL) is a form of non-Hodgkin lymphoma that rarely affects skin. Cutaneous involvement is non-specific but usually indicates widespread disease. Herein we present two cases of MCL with secondary skin involvement. One case presented as an acneiform eruption on the face and had aberrant expression of bcl-2 and bcl-6 with weak CD5 expression. The second presented with multiple tumors on the abdomen and thighs. In both cases expression of Cyclin-D1 by the tumor cells was seen. Both patients died shortly after the diagnosis was established.